By-Laws for the section on Archives and Human Rights - ICA Executive Board (2019)

Community-Based Transitional Justice Via the Creation and Consumption of Digitalized Storytelling Archives: A Case Study of Belfast’s Prisons Memory Archive - Anderson, Michelle (International Journal of Transitional Justice, 2019)
Other Publications

Oral History and Collective Memory: Documenting Refugee Voices and the Challenges of Archival Representation - Dudman, Paul (Atlanti, 2019)

Digital LGBTQ archives as sites of public memory and pedagogy - Van Haitsma, Pamela (Rhetoric and Public Affairs, 2019)
Other Publications

Moving past: probing the agency and affect of recordkeeping in individual and community lives in post-conflict Croatia - J. Gilliland, Anne (Archival Science, 2014)
Reporting on ongoing research, this paper reviews stories, drawn from recent literature as well as gathered through ethnographic research, that people tell about records and recordkeeping during and since the Yugoslav Wars. It focuses on what these stories reveal of the agency and affect of recordkeeping in individual and community lives, particularly in Croatia. The paper concludes with a contemplation of what might be learned from such an approach for the development of recordkeeping infrastructures that can anticipate, avert or alleviate some of the ways in which records and recordkeeping continue to traumatize or target the vulnerable, and frustrate and prevent the human and societal need to “move forward,” if not “move past.”
Other Publications
Keywords: A&DwP website

Twenty years of post-apartheid archiving: have we reckoned with the past, or has the past reckoned with us? - Harris, Verne (Journal of the South African Society of Archivists, 2014)
Other Publications
Keywords: A&DwP website

Archives for a Peaceful Future: Case Descriptions - Jones, Briony; Keller, Ingrid Oliveira Silva; Rubli, Sandra (2014)
Other Publications

Archives as agents of accountability and justice: an examination of the national security archive in the context pf transitional justice in Latin America. - Blanco-Rivera, Joel A (Dissertation. Graduate Faculty of School of Information Sciences, University of Pittsburgh, 2012)
Other Publications

Accountability in archival science since Parkinson’s thesis - Kenosi, Lekoko (Comma, International Journal on Archives, 2012)
Other Publications
Keywords: A&DwP website

Human Rights, Human Wrongs, and Archives / Derechos humanos, injusticias humanas y archivos - Peterson, Trudy Huskamp (Arch-E. Revista Andaluza de Archivos, 2012)
The focus on wrongs —evil, crimes against humanity, disappearances, genocide— and the archival records of wrongs is fundamentally important and we must not lose sight of that. But by looking at the phrase “archives and human rights” in only those terms, we miss the hugely important sets of records that are not related to State crimes, not in the hands of the state, and are vital to protect—not only to contest the loss of—human rights.
Keywords: A&DwP website

The potential and challenges of open data for crisis information management and aid efficiency - Stauffacher, Daniel; Hattotuwa, Sanjana; Weekes, Barbara (ICT for Peace Foundation, 2012)
Other Publications
Keywords: A&DwP website

Secrets and Files: Access to Archives in Italy from WWII to the Present - Barrera, Giulia (Acervo. Revista do Arquivo Nacional, 2011)
Other Publications

Admissibility of electronic documentation as evidence in U.S. courts - Thomson, Lucy L (Human Rights Electronic Evidence Study, Center for Research Libraries, 2011)
Other Publications

Basic principles on the role of archivists and records managers in support of human rights - International Council on Archives; Human Rights Working Group (International Council on Archives, 2016)

My Life as a Spy: Investigations in a Secret Police File - Verdery, Katherine (Duke Univ Pr, 2018)
As Katherine Verdery observes, "There's nothing like reading your secret police file to make you wonder who you really are." In 1973 Verdery began her doctoral fieldwork in the Transylvanian region of Romania, ruled at the time by communist dictator Nicolae Ceausescu. She returned several times over the next twenty-five years, during which time the secret police–the Securitate–compiled a massive surveillance file on her. Reading through its 2,781 pages, she learned that she was "actually" a spy, a CIA agent, a Hungarian agitator, and a friend of dissidents: in short, an enemy of Romania. In My Life as a Spy she analyzes her file alongside her original field notes and conversations with Securitate officers. Verdery also talks with some of the informers who were close friends, learning the complex circumstances that led them to report on her, and considers how fieldwork and spying can be easily confused. Part memoir, part detective story, part anthropological analysis, My Life as a Spy offers a personal account of how government surveillance worked during the Cold War and how Verdery experienced living under it.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Transitional Justice in Eastern Europe and the former Soviet Union: Reckoning with the communist past - Stan, Lavinia (Routledge, 2010)
During the last two decades, the countries of Eastern Europe and the former Soviet Union have attempted to address the numerous human rights abuses that characterized the decades of communist rule. This book examines the main processes of transitional justice that permitted societies in those countries to come to terms with their recent past. It explores lustration, the banning of communist officials and secret political police officers and informers from post-communist politic, ordinary citizens’ access to the remaining archives compiled on them by the communist secret police, as well as trials and court proceedings launched against former communist officials and secret agents for their human rights trespasses. Individual chapters explore the progress of transitional justice in Germany, the Czech Republic, Slovakia, Poland, Hungary, Romania, Bulgaria, Albania, Slovenia and the successor states of the former Soviet Union. The chapters explain why different countries have employed different models to come to terms with their communist past; assess each country’s relative successes and failures; and probe the efficacy of country-specific legislation to attain the transitional justice goals for which it was developed. The book draws together the country cases into a comprehensive comparative analysis of the determinants of post-communist transitional justice, that will be relevant not only to scholars of post-communist transition, but also to anyone interested in transitional justice in other contexts.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Post-Communist Transitional Justice: Lessons from Twenty-Five Years of Experience - Stan, Lavinia; Nedelsky, Nadya (Cambridge University Press, 2015)
Taking stock of the twenty-fifth anniversary of the collapse of the communist regimes of Central and Eastern Europe, this volume explores the ways these societies have grappled with the serious human rights violations of past regimes. It focuses on the most important factors that have shaped the nature, speed, and sequence of transitional justice programs in the period spanning the tumultuous revolutions that brought about the collapse of the communist dictatorships and the consolidation of new democratic regimes. Contributors explain why leaders made certain choices, discuss the challenges they faced, and explore the role of under-studied actors and grassroots strategies. Written by recognized experts with an unparalleled grasp of the region's communist and post-communist reality, this volume addresses far-reaching reckoning, redress, and retribution policy choices. It is an engaging and carefully crafted volume, and it covers a wide variety of cases and discusses key transitional justice theories using both qualitative and quantitative research methods.
Keywords: References - Boel et al. (2021); Archives and Human Rights

The History of the Stasi: East Germany's Secret Police, 1945-1990 - Gieseke, Jens (Berghahn Books, 2015)
A well-balanced and detailed look at the East German Ministry for State Security, the secret police force more commonly known as the Stasi. “This is an excellent book, full of careful, balanced judgements and a wealth of concisely-communicated knowledge. It is also well written. Indeed, it is the best book yet published on the MfS.”―German History The Stasi stood for Stalinist oppression and all-encompassing surveillance. The “shield and sword of the party,” it secured the rule of the Communist Party for more than forty years, and by the 1980s it had become the largest secret-police apparatus in the world, per capita. Jens Gieseke tells the story of the Stasi, a feared secret-police force and a highly professional intelligence service. He inquires into the mechanisms of dictatorship and the day-to-day effects of surveillance and suspicion. Masterful and thorough at once, he takes the reader through this dark chapter of German postwar history, supplying key information on perpetrators, informers, and victims. In an assessment of post-communist memory politics, he critically discusses the consequences of opening the files and the outcomes of the Stasi debate in reunified Germany. A major guide for research on communist secret-police forces, this book is considered the standard reference work on the Stasi.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Transitional Justice after German Reunification: Exposing Unofficial Collaborators - Espindola, Juan (Cambridge University Press, 2015)
How do societies transitioning from oppressive to democratic rule hold accountable those citizens who contributed to maintaining injustice in the ancient regime by secretly denouncing fellow citizens? Is their public identification a way of fulfilling respect for those who suffered harm as a result of their collaboration? And is public identification respectful of denunciators themselves? This book pursues these questions through a multidisciplinary investigation focusing on the denunciators for the East German secret police and the Ministry of State Security and the way in which they have been publicly unveiled in contemporary German society. The book evaluates the justifications that social actors offer to support or oppose public identifications; how targeted collaborators react to this social practice; and whether it achieves its intended purpose. At every stage, the book asks whether the motivations and the consequences of public identifications honor or undermine the value of respect for people.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Iron Curtain: The Crushing of Eastern Europe, 1944-1956 - Applebaum, Anne (Knopf Doubleday Publishing Group, 2013)
National Book Award Finalist TIME Magazine's #1 Nonfiction Book of 2012A New York Times Notable BookA Washington Post Top Ten Book of 2012Best Nonfiction of 2012: The Wall Street Journal, The Plain Dealer In the much-anticipated follow-up to her Pulitzer Prize-winning Gulag, acclaimed journalist Anne Applebaum delivers a groundbreaking history of how Communism took over Eastern Europe after World War II and transformed in frightening fashion the individuals who came under its sway. Iron Curtain describes how, spurred by Stalin and his secret police, the Communist regimes of Eastern Europe were created and what daily life was like once they were complete. Drawing on newly opened East European archives, interviews, and personal accounts translated for the first time, Applebaum portrays in chilling detail the dilemmas faced by millions of individuals trying to adjust to a way of life that challenged their every belief and took away everything they had accumulated. As a result the Soviet Bloc became a lost civilization, one whose cruelty, paranoia, bizarre morality, and strange aesthetics Applebaum captures in these electrifying pages.
Keywords: References - Boel et al. (2021); Archives and Human Rights

History textbooks and the wars in Asia: divided memories - Shin, Gi-Wook; Sneider, Daniel C. (Routledge, 2011)
OCLC: ocn651914367
Keywords: 20th century; East Asia; Historiography; History; Military Historiography; History; Military Study and teaching (Secondary); History; Military Textbooks; Nationalism and education; Nationalism and historiography; References - Boel et al. (2021); Archives and Human Rights; Social aspects

The History Problem: The Politics of War Commemoration in East Asia - Saito, Hiro (University of Hawaii Press, 2016)
Seventy years have passed since the end of the Asia-Pacific War, yet Japan remains embroiled in controversy with its neighbors over the war’s commemoration. Among the many points of contention between Japan, China, and South Korea are interpretations of the Tokyo War Crimes Trial, apologies and compensation for foreign victims of Japanese aggression, prime ministerial visits to the Yasukuni Shrine, and the war’s portrayal in textbooks. Collectively, these controversies have come to be called the “history problem.” But why has the problem become so intractable? Can it ever be resolved, and if so, how? To answer these questions author Hiro Saito mobilizes the sociology of collective memory and social movements, political theories of apology and reconciliation, psychological research on intergroup conflict, and philosophical reflections on memory and history. The history problem, he argues, is essentially a relational phenomenon caused when nations publicly showcase self-serving versions of the past at key ceremonies and events: Japan, South Korea, and China all focus on what happened to their own citizens with little regard for foreign others. Saito goes on to explore the emergence of a cosmopolitan form of commemoration taking humanity, rather than nationality, as its primary frame of reference, an approach increasingly used by a transnational network of advocacy NGOs, victims of Japan’s past wrongdoings, historians, and educators. When cosmopolitan commemoration is practiced as a collective endeavor by both perpetrators and victims, Saito argues, a resolution of the history problem—and eventual reconciliation—will finally become possible.The History Problem examines a vast corpus of historical material in both English and Japanese, offering provocative findings that challenge orthodox explanations. Written in clear and accessible prose, this uniquely interdisciplinary book will appeal to sociologists, political scientists, and historians researching collective memory, nationalism and cosmopolitanism, and international relations—and to anyone interested in the commemoration of historical wrongs.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Sorry States: Apologies in International Politics - Lind, Jennifer (Cornell University Press, 2010)
Governments increasingly offer or demand apologies for past human rights abuses, and it is widely believed that such expressions of contrition are necessary to promote reconciliation between former adversaries. The post-World War II experiences of Japan and Germany suggest that international apologies have powerful healing effects when they are offered, and poisonous effects when withheld. West Germany made extensive efforts to atone for wartime crimes-formal apologies, monuments to victims of the Nazis, and candid history textbooks; Bonn successfully reconciled with its wartime enemies. By contrast, Tokyo has made few and unsatisfying apologies and approves school textbooks that whitewash wartime atrocities. Japanese leaders worship at the Yasukuni Shrine, which honors war criminals among Japan's war dead. Relations between Japan and its neighbors remain tense.Examining the cases of South Korean relations with Japan and of French relations with Germany, Jennifer Lind demonstrates that denials of past atrocities fuel distrust and inhibit international reconciliation. In Sorry States, she argues that a country's acknowledgment of past misdeeds is essential for promoting trust and reconciliation after war. However, Lind challenges the conventional wisdom by showing that many countries have been able to reconcile without much in the way of apologies or reparations. Contrition can be highly controversial and is likely to cause a domestic backlash that alarms?rather than assuages?outside observers. Apologies and other such polarizing gestures are thus unlikely to soothe relations after conflict, Lind finds, and remembrance that is less accusatory-conducted bilaterally or in multilateral settings-holds the most promise for international reconciliation.
Keywords: References - Boel et al. (2021); Archives and Human Rights

NARRATIVES AND BILATERAL RELATIONS: RETHINKING THE “HISTORY ISSUE” IN SINO- JAPANESE RELATIONS - Gustafsson, Karl (Stockholm University, 2011)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Contested Memories in Chinese and Japanese Foreign Policy - Dian, Matteo (Chandos Publishing, 2017)
Contested Memories in Chinese and Japanese Foreign Policy explores the issue of memory and lack of reconciliation in East Asia. As main East Asian nations have never achieved a common memory of their pasts, in particular, the events of the Second World War and Sino-Japanese War, this book locates the issue of memory within International Relations theory, exploring the theoretical and practical link between the construction of a country’s identity and the formation and contestation of its historical memory and foreign policy.Provides an innovative theoretical frameworkDraws connections between the role of memory and foreign policyUses the interpretative theory of international relationsGives comparative perspective using the cases of China and JapanPresents in-depth analysis of the construction and contestation of national memory in China and Japan
Keywords: References - Boel et al. (2021); Archives and Human Rights

Political Survival and Yasukuni in Japan's Relations with China - Cheung, Mong (Routledge, 2018)
What role does the political survival of prime ministers play in Japan’s relations with China over the Yasukuni issue? Three Japanese prime ministers, including Nakasone Yasuhiro, Hashimoto Ryutaro and Abe Shinzo, complied with China’s demands and stopped visiting the controversial Shrine in 1986, 1997 and 2007, respectively. By contrast, the Yasukuni controversy intensified between 2001 and 2006 when a popular Prime Minister Koizumi Junichiro was determined to pay regular homage to the Yasukuni Shrine annually. Prime Minister Abe, who previously demonstrated restraint over the issue in his first term between 2006 and 2007, visited the Yasukuni unexpectedly in 2013 but not in 2014 or 2015. To explain this variation, this book presents an alternative interpretation of Japan’s official responses toward China’s pressure over the Yasukuni issue between 1985 and 2015 by applying a political survival approach that highlights the domestic political legitimacy of the Japanese prime minister or the ruling party.This book will be of great interest to students and researchers of Sino-Japanese relations, Japan’s foreign policy and international relations.
Keywords: References - Boel et al. (2021); Archives and Human Rights

China: The Pessoptimist Nation - Callahan, William A. (Oxford University Press, 2012)
The rise of China presents a long-term challenge to the world not only economically, but politically and culturally. Callahan meets this challenge in China: The Pessoptimist Nation by using new Chinese sources and innovative analysis to see how Chinese people understand their new place in the world.To chart the trajectory of its rise, the book shifts from examining China's national interests to exploring its national aesthetic. Rather than answering the standard social science question "what is China?" with statistics of economic and military power, this book asks "when, where, and who is China?" to explore the soft power dynamics of China's identity politics.China: The Pessoptimist Nation shows how the heart of Chinese foreign policy is not a security dilemma, but an identity dilemma. Through careful analysis, Callahan charts how Chinese identity emerges through the interplay of positive and negative feelings in a dynamic that intertwines China's domestic and international politics. China thus is the pessoptimist nation where national security is closely linked to nationalist insecurities.Callahan concludes that this interactive view of China's pessoptimist identity means that we need to rethink the role of the state and public opinion in Beijing's foreign policy-making.
Keywords: References - Boel et al. (2021); Archives and Human Rights

The Gacaca Courts, Post-Genocide Justice and Reconciliation in Rwanda: Justice without Lawyers - Clark, Phil (Cambridge University Press, 2010)
This is a timely empirical study and review of the Gacaca Courts which were established in 2001 in Rwanda as an attempt to prosecute suspects involved in the 1994 genocide. Based on the author's original field work which began in 2003 in Rwanda and which has been updated to the end of 2009, it includes responses from within the Rwandan population. Dr. Clark argues that, despite widespread international scepticism, the Gacaca process has achieved remarkable results in terms of justice and reconciliation, although this has often come at a price, especially the re-traumatisation of many Rwandans who have participated firsthand in hearings. This book will appeal to a wide global readership crossing human rights, transitional justice and African studies for its combination of original empirical data with a socio-legal analysis.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Unspeakable Truths: Transitional Justice and the Challenge of Truth Commissions - Hayner, Priscilla B. (Routledge, 2010)
In a sweeping review of forty truth commissions, Priscilla Hayner delivers a definitive exploration of the global experience in official truth-seeking after widespread atrocities. When Unspeakable Truths was first published in 2001, it quickly became a classic, helping to define the field of truth commissions and the broader arena of transitional justice. This second edition is fully updated and expanded, covering twenty new commissions formed in the last ten years, analyzing new trends, and offering detailed charts that assess the impact of truth commissions and provide comparative information not previously available.Placing the increasing number of truth commissions within the broader expansion in transitional justice, Unspeakable Truths surveys key developments and new thinking in reparations, international justice, healing from trauma, and other areas. The book challenges many widely-held assumptions, based on hundreds of interviews and a sweeping review of the literature. This book will help to define how these issues are addressed in the future.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Political Effects: Trust in Government - Roman, David (Lustration and Transitional Justice: Personnel Systems in the Czech Republic, Hungary, and Poland., 2011)
Keywords: References - Boel et al. (2021); Archives and Human Rights

The United Nations Set of Principles to Combat Impunity: A Commentary - Haldemann, Frank; Unger, Thomas (Oxford University Press, 2018)
The fight against impunity has become a growing concern of the international community. Updated in 2005, the UN Set of Principles for the Protection and Promotion of Human Rights Through Action to Combat Impunity is the fruit of several years of study, developed under the aegis of the UN Commission on Human Rights and then affirmed by the Human Rights Council. These Principles are today widely accepted as constituting an authoritative reference point for efforts in the fight against impunity for gross human rights abuses and serious violations of international humanitarian law. As a comprehensive attempt to codify universal accountability norms, the UN Set of Principles marks a significant step forward in the debate on the obligation of states to combat impunity in its various forms. Bringing together leading experts in the field, this volume provides comprehensive academic commentary of the 38 principles. The book is a perfect companion to the document, setting out the text of the Principles alongside detailed analysis, as well as a full introduction and a guide to the relevant literature and case law. The commentary advances debates and clarifies complex legal issues, making it an essential resource for legal academics, students, and practitioners working in fields such as human rights, international criminal law, and transitional justice.
Keywords: References - Boel et al. (2021); Archives and Human Rights

A Paper Monument: The History of the Arolsen Archive - Borggräfe, Henning; Höschler, Christian; Panek, Isabel; Arolsen Archives (Bad Arolsen, 2019)
Keywords: References - Boel et al. (2021); Archives and Human Rights

solution adopted by the Human Rights Council - 18/7 Special Rapporteur on the promotion of truth, justice, reparation and guarantees of non-recurrence - Human Rights Council (United Nations, 2011)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Austerlitz - Sebald, W.G. (Penguin, 2010)
Keywords: References - Boel et al. (2021); Archives and Human Rights

The Emergence of Memory: Conversations with W. G. Sebald - Sebald, W. G. (Seven Stories Press, 2010)
When German author W. G. Sebald died in a car accident at the age of fifty-seven, the literary world mourned the loss of a writer whose oeuvre it was just beginning to appreciate. Through published interviews with and essays on Sebald, award-winning translator and author Lynne Sharon Schwartz offers a profound portrait of the writer, who has been praised posthumously for his unflinching explorations of historical cruelty, memory, and dislocation. With contributions from poet, essayist, and translator Charles Simic, New Republic editor Ruth Franklin, Bookworm radio host Michael Silverblatt, and more, The Emergence of Memory offers Sebald’s own voice in interviews between 1997 up to a month before his death in 2001. Also included are cogent accounts of almost all of Sebald’s books, thematically linked to events in the contributors’ own lives.Contributors include Carole Angier, Joseph Cuomo, Ruth Franklin, Michael Hofmann, Arthur Lubow, Tim Parks, Michael Silverblatt, Charles Simic, and Eleanor Wachtel.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Identifying Culturally Sensitive American Indian Material in a Non-tribal Institution - Ryan, Ellen M (Society of American Archivists, 2014)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Proof - Peterson, Trudy Huskamp (Informatio, 2018)
This essay looks at the historical background of compensation payments, then considers the impact of World War II on reparations programs, the intellectual criteria for compensation developed by international bodies during the second half of the 20th century, and examples of state-level compensation after 1975 to individuals who were harmed by state actions. It concludes by considering the documents required to prove identity and prove the harm that gives rise to the right to compensation.
Keywords: References - Boel et al. (2021); Archives and Human Rights; References - Comma (2020 1-2); Archives and Human Rights

René Cassin and Human Rights: From the Great War to the Universal Declaration - Winter, Jay; Prost, Antoine (Cambridge University Press, 2013)
Through the life of one extraordinary man, this biography reveals what the term human rights meant to the men and women who endured two world wars, and how this major political and intellectual movement ultimately inspired and enshrined the Universal Declaration of Human Rights. René Cassin was a man of his generation, committed to moving from war to peace through international law, and whose work won him the Nobel Peace Prize in 1968. His life crossed all the major events of the first seventy years of the twentieth century, and illustrates the hopes, aspirations, failures and achievements of an entire generation. It shows how today's human rights regimes emerged from the First World War as a pacifist response to that catastrophe and how, after 1945, human rights became a way to go beyond the dangers of absolute state sovereignty, helping to create today's European project.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

News from the ICA Human Rights Working Group - 2017-10 (October) - Peterson, Trudy Huskamp (ICA, 2017)
Keywords: Oct'17 newsletter link to Nov'17.

News from the ICA Human Rights Working Group - 2016-03 (March) - Peterson, Trudy Huskamp (ICA, 2016)
Keywords: Mar'16 shows the link to Apr'16

News from the ICA Human Rights Working Group - 2015-09 (September) - Peterson, Trudy Huskamp (ICA, 2015)
Keywords: Sep'15 Newsletter has Oct'15 Newsletter in it. No Sep'15 newsletter